APLIKASI PENAMBAHAN ENZIM PAPAIN PADA PAKAN UNTUK IKAN TAMBAKAN (Helostoma temminckii) DI DESA PULAU SEMAMBU KABUPATEN OGAN ILIR - Dade Jubaedah; Dwi Rizki Septiana; Yulisman Yulisman; Ferdinand Hukama Taqwa; Marini Wijayanti; Mirna Fitrani; Sefti Heza Dwinanti; Madyasta Anggana Rarassari (Jurnal Abdi Insani, 2022)
The Fish Under Crew Cultivator Group is located in Pulau Semambu Village which was established in 2016 with fish commodities, including fish ponds. The aquacultured fish can already respond to the artificial feed given. However, the use of feed by the aquaculture fish is still not efficient. This is a problem faced by fish farmers, including in the Fish Under Crew group. The addition of papain enzymes in feed can increase feed digestibility so that fish can utilize feed more efficiently. The purpose of this community service activity is to apply the use of the papain enzyme in artificial feed to increase feed digestibility and its effect on the growth and production of aquaculture fish. Methods of activity include: 1) socialization of activities, 2) counseling to group members and the community in Pulau Semambu Village, 3) providing assistance in the form of two tarpaulin ponds with iron frames and their accessories, 4) Application of board enzymes to fish through fish rearing activities for 1 year. months, using two treatments, namely 0% papain enzyme in feed as control (P0) and 0.75% papain enzyme in feed (P1). Socialization and counseling were carried out by involving group members and the community in Pulau Semambu Village. The community understands the extension material presented and is very enthusiastic to apply it in their cultivation activities as evidenced by very interactive question and answer sessions during the discussion session and answers to the questionnaires given to participants. The pool assistance was received by group members, accompanied by village officials and Bumdesma administrators. In fish rearing by applying the addition of papain enzyme to feed, it gave a higher absolute growth rate (absolute weight growth 0.41 g and absolute length 0.56 cm) than commercial feed without the addition of papain enzyme. Based on the activities that have been carried out, UPR Fish Under Crew has applied the addition of papain enzymes to feed for aquaculture fish. The results obtained can increase the growth of the pond fish that are kept and the use of feed is more efficient.